2014
DOI: 10.1007/s11743-014-1613-2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Study of Anionic Surfactant with Aqueous Non‐Ionic Polymers from Conductivity, Density and Speed of Sound Measurements

Abstract: In the present study, we have investigated in detail the interactions of the anionic surfactant sodium dodecyl sulfate (SDS) with aqueous polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP) and various PEG ? PVP mixtures at 293.15, 303.15 and 313.15 K by applying conductivity, density and speed of sound techniques. From experimentally measured data, the critical micelle concentration (CMC) values, standard free energy of micellization (DG m o ), standard enthalpy of micellization (DH m o ), standard entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…It is found that c 1 is equal to 2.4 ± 0.1 mM independent of PVP mass concentration (q PVP ), whereas c 2 rises with the increase of q PVP . This result is in agreement with our previous discovery obtained from tensiometry [35] listed in the right column of Table 1 as control, and also consistent with other reports [36,37]. Fang et al [38] suggested using ''the specific saturation capacity of clusterization [U 1 ]" to describe the maximum amount of the micelle-like surfactant molecules aggregating on polymer chains.…”
Section: Methodssupporting
confidence: 92%
“…It is found that c 1 is equal to 2.4 ± 0.1 mM independent of PVP mass concentration (q PVP ), whereas c 2 rises with the increase of q PVP . This result is in agreement with our previous discovery obtained from tensiometry [35] listed in the right column of Table 1 as control, and also consistent with other reports [36,37]. Fang et al [38] suggested using ''the specific saturation capacity of clusterization [U 1 ]" to describe the maximum amount of the micelle-like surfactant molecules aggregating on polymer chains.…”
Section: Methodssupporting
confidence: 92%
“…That is, micelles form in the solution spontaneously, which shows that interactions are voluntary. The sign of ∆H informs us on the nature of ΔS_2% micellization mechanism, in other words on whether it is endothermic or exothermic [46]. Positive ∆H value may emphasize importance of hydrophobic interaction while negative ∆H value shows that the major attraction force for micellization exhibits London dispersion interaction [47].…”
Section: Discussionmentioning
confidence: 99%
“…entropy. At lower temperatures the positive normalΔSmo values can be recommended due to release of prearranged solvent molecules from the hydrophobic (non‐polar) part of the surfactant and that is the foremost attractive force for micelle formation via aquaphobic interactions (Chauhan et al, 2015).…”
Section: Resultsmentioning
confidence: 99%